Visionary Leadership Of Madrasah Principals In Improving Students' Academic And Non-Academic Achievements At MAS AL-Muslimun - Idayanti, Mira; Almuhajir, Almuhajir; Fauzan, Fauzan (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
ABSTRACTÂ The achievements obtained by the MAS Al-Muslimun institution under the leadership of the current head of the madrasa make it one of the pioneers of madrasas in North Aceh. Having differentiators in educational institutions can certainly be used as a strategy and stepping stone to introduce these institutions to the public. The aim of this research is to explain the characteristics of the visionary leadership of the head of MAS Al-Muslimun, the efforts of the madrasah head in improving the academic and non-academic achievements of students, and explain the supporting and inhibiting factors in improving the academic and non-academic achievements of students at MAS Al-Muslimun. The research method used is qualitative with a qualitative descriptive approach. Data collection techniques were carried out using interviews, documentation and observation. The research results show that the visionary leadership characteristics of the head of MAS Al-Muslimun are always having a plan, being completely ambitious about target results, socialising the vision and mission, controlling his subordinates to get a support system, and exploring existing resources to support the vision and mission programme. The madrasa head's efforts to improve the academic and non-academic achievements of students at MAS Al-Muslimun include planning, implementation, evaluation and follow-up. Supporting factors in increasing student achievement at MAS Al-Muslimun are influenced by internal and external factors, while inhibiting factors are the lack of teacher resources who are experts in their fields to guide and train students, there is still a lack of teachers who have a lot of information to increase competitiveness and student achievement, as well as more support from parents in supporting student achievement.Â Keywords: Visionary Leadership, Madrasah Head, Academic and Non-Academic Achievement